Adsorption and Desorption of Steroid Hormones by Microplastics in Seawater - Lu, Jian; Wu, Jie; Wu, Jun; Zhang, Cui; Luo, Yongming (Bulletin of environmental contamination and toxicology, 2021)
This study evaluated the adsorption and desorption of 17β-estradiol (E2) and 17α-ethynylestradiol (EE2) on microplastics in seawater. The effects of microplastic materials and particle sizes on adsorption of E2 and EE2 were explored. Moreover, effects of salinity, pH, humic acid (HA) concentrations, and initial E2/EE2 concentrations on adsorption were also discussed. Increase in salinity, HA concentration, and initial E2/EE2 concentration would enhance adsorption of E2/EE2 on microplastics. Adsorption capacity of E2/EE2 firstly increased to reach the highest at pH of 8.0 and then decreased when pH further increased. Pseudo-second-order kinetics better fitted adsorption data of E2 while pseudo-first-order model yielded better fitting results for EE2. Freundlich isotherm was better to fit the adsorption data of E2 while Langmuir isotherm yielded better fitting results for EE2. Desorption capacity of E2/EE2 on microplastics was over 40% of its adsorption capacity. This study provides new insights on microplastics and endocrine disrupting chemicals.